Selenium induces changes in the selenocysteine tRNA[Ser]Sec population in mammalian cells. - Hatfield, D (1991)
Two isoacceptors of selenocysteine tRNA[Ser]Sec are present in higher vertebrates which are responsible for donating selenocysteine to protein. One such selenocysteine containing protein, glutathione peroxidase, requires selenium for its translation and transcription. Since tRNA[Ser]Sec is a critical component of the glutathione peroxidase translational machinery, the levels and distributions of its isoacceptors were examined from both human and rat cells grown in chemically defined media with and without selenium. Not only did the level of the selenocysteine tRNA[Ser]Sec population increase approximately 20% in cells grown in the presence of selenium, but the distributions of the two isoacceptors also changed relative to each other.